Revolutionary violence - "Mohanty, Manoranjan" (New Delhi, 1977)
Some accounts of the "Naxalite Movement " in India are already available. This one makes a few departures. This is a study by a student of Chinese politics and it forms a part of a larger project on the theory and practice of Mao Tse-tung's ideology.
Keywords: Revolutions